On path following control of nonholonomic mobile manipulators - Mazur, Alicja; Szakiel, Dawid (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the problem of designing control laws for path following robots, including two types of nonholonomic mobile manipulators. Due to a cascade structure of the motion equation, a backstepping procedure is used to achieve motion along a desired path. The control algorithm consists of two simultaneously working controllers: the kinematic controller, solving motion constraints, and the dynamic controller, preserving an appropriate coordination between both subsystems of a mobile manipulator, i.e. the mobile platform and the manipulating arm.
Keywords: mobile manipulator; nonholonomic constraints; path following; Frenet parametrization